Movement From Emerging Economies to Small Island States: Motivations of Nigerian Educational Tourists in North Cyprus - Cahit Ezel; Huseyin Arasli (Island Studies Journal, 2021)
Although core countries, in particular the UK, USA, Canada, and Australia, have been the most popular destinations for educational tourism, a substantial number of educational tourists have recently been travelling to other European, Asian, and African countries. There has been significant research into student mobility from developing countries to core countries, but research on student mobility between developing countries—in particular the movement from emerging economies to small island states—is scarce. North Cyprus has recently become a thriving international educational tourism destination. This study explores the factors affecting educational tourists’ decision-making, with a specific focus on Nigerian students, about whom very little is known regarding their decision to study abroad and their choices of host country and host university. Data from a qualitative study carried out in the small island state of North Cyprus is used to examine the factors that push Nigerian educational tourists away from their home country to seek tertiary education opportunities elsewhere as well as the factors affecting their host country and host institution choices. Three main themes emerged from the data analysis, namely: Studying Overseas, Country Choice, and Host Institution. The results of this study are useful for policymakers in small island states, who wish to establish or improve an educational tourism industry, as well as for university decision-makers who wish to increase their institutions’ success at attracting foreign students.